The Fall of the Caliphate of Córdoba : Berbers and Andalusis in Conflict - Scales, Peter C., (Medieval Iberian Peninsula ;, 1994)
This book is a discussion of the complex events which surround the breakup of the Muslim Caliphate of Córdoba in the early eleventh century. The focus of the study concerns quite a short period of time: 1009-1031 A.D., although a wide-ranging investigation of the political structure of Muslim Spain is embarked on. A thorough narrative of the events is followed by separate discussions of some of the main groups involved in the civil wars, the Marwānids (the supporters of a legitimately-appointed Umayyad representative), the saqāliba (Slavs), the Berbers and the Christians of northern Spain. This book is able to fill the gap in our knowledge of this hitherto little-understood period of Spanish history and tackles important questions, such as the attitude towards the Berbers, tribal solidarity and the importance of land-reforms during the 10th century